Pengaruh Relaksasi Otot Progresif Terhadap Penurunan Nyeri Punggung Bagian Bawah Ibu Hamil Trimester III di Wilayah Kerja Puskesmas Malifut Kabupaten Halmahera Utara - Irmawati.S; Rosdiana Rosdiana; Yuniarti Ibrahim (NAJ Nursing Applied Journal, 2024)
Pregnancy is a very important experience for a woman. Based on the journal Of Midwifery issued in 2020, it is stated that lower back pain is the most common complaint in the third trimester of pregnancy. Predisposing factors for back pain include uterine growth which causes changes in posture, weight gain, the influence of the relaxin hormone on ligaments, previous history of back pain, parity and activity. Research Objective: to determine the effect of progressive muscle relaxation on lower back pain in third trimester pregnant women at the Malifut Community Health Center. This type of research is experimental research involving one group of subjects with a pre-experimental approach, one group pretest posttest design. The respondents for this research were 30 people. Purposive sampling technique. Results: This study showed that 30 respondents who had not been treated with progressive muscle relaxation techniques experienced moderate pain as many as 18 people (60%) and experienced mild pain as many as 12 people (40%). Shows that 30 people (100%) experienced a reduction in pain. The results after it was discovered that the Wilcoxon test was carried out above the P value = 0.000 (< 0.05) so that there was a significant difference between lower back pain before the relaxation intervention was given. Advice for pregnant women who experience levels of pain is to carry out progressive muscle relaxation to reduce the level of lower back pain